Intra- and inter-host origin, evolution dynamics and spatial-temporal transmission characteristics of circoviruses - Cui, Yongqiu; Li, Siting; Xu, Weiying; Xie, Jiali; Wang, Dedong; Hou, Lei; Zhou, Jianwei; Feng, Xufei; Liu, Jue (Frontiers in Immunology, 2024)
Since their identification in 1974, circoviruses have caused clinicopathological diseases in various animal species, including humans. However, their origin, transmission, and genetic evolution remain poorly understood. Here, the evolutionary origin, mode of transmission, and genetic recombination of the circovirus were determined based on the available circovirus genome sequences. The origin of circoviruses can be traced back to fish circovirus, which might derive from fish genome, and human contributes to transmission of fish circovirus to other species. Furthermore, mosquitos, ticks, bats, and/or rodents might play a role as intermediate hosts in circovirus intra-and inter-species transmission. Two major lineages (A and B) of circoviruses are identified, and frequent recombination events accelerate their variation and spread. The time to the most recent common ancestor of circoviruses can be traced back to around A.D. 600 and has been evolving at a rate of 10 -4 substitutions site -1 year - 1 for a long time. These comprehensive findings shed light on the evolutionary origin, population dynamics, transmission model, and genetic recombination of the circovirus providing valuable insights for the development of prevention and control strategies against circovirus infections.